Spatial-temporal characteristics and influencing factors of food production efficiency based on WEF nexus in China. (1st January 2022) - Zheng, Defeng; An, Zhiying; Yan, Chenglin; Wu, Rina
Abstract: Water, energy, and food (WEF) are essential material bases for mankind's survival and development. At the same time, water and energy, as necessary inputs for food production, are of great significance to food security. Scientific understanding of the water-energy-food nexus (WEF Nexus) in food production is conducive to ensuring food security and sustainable utilization of basic resources. However, current research linking the WEF Nexus with food production is lacking. Therefore, we took the WEF Nexus as an entry point to quantify China's food production efficiency and considered the direct and indirect inputs of water and energy in food production in this paper. First, we constructed an evaluation index system of food production efficiency based on the perspective of input-output and used the stochastic frontier production function model to measure the absolute efficiency values of food production. Then, GIS spatial analysis, spatial autocorrelation analysis, and the gravity center model were used to reveal the spatial-temporal pattern, spatial autocorrelation characteristics and barycenter trajectory, respectively. Finally, the Tobit model was applied to analyze the main factors which influenced the spatial pattern changes of food production efficiency. The research results indicated that China's food production efficiency was on the rise and there were spatial differences between provinces. Per capita GDP, natural disaster losses and irrigated areas of food crops were the main factors influencing China's food production efficiency. This paper contributed a new theoretical reference to the study of food production efficiency, and provided a decision-making reference for regional resource management to ensure basic resource security and sustainable development in the future. Graphical abstract: Image 1 Highlights: Taking WEF Nexus as an entry point to quantify China's food production efficiency based on SFA model. Analyzing the temporal and spatial characteristics and influencing factors of China's food production efficiency. China's food production efficiency was on the rise and there are spatial differences between provinces from 2000 to 2018. The paper made reasonable policy recommendations in view of China's food production efficiency current situation.